Lipid peroxide level and antioxidant defense in experimental lead neurotoxicity in rats - PATRA, R C; SWARUP, D; DWIVEDI, S K; SAHOO, A (The Indian Journal of Animal Sciences, 2014)
An experiment was carried out with 48 IVRI 2CQ rats to study the post- exposure effects of lead on the selected parameters indicative of oxidative damage, ,and on the thiol contents in the brain. Rats (24) were given a daily dose @ 1 mg lead/ 2 ml of distilled water/ kg .body weight for 30 day through an intraperitoneal route. Rats (24) receiving sterile normal saline solution served as negative controls. The intraperitoneal injections were withdrawn and 6 rats [rom each group were sacrificed at the end of the exposure (day 0) and thereafter on days 3, 7 and 10. The activities of antioxidant enzymes, such as superoxide dismutase and catalase, the levels of lipid peroxides and thiol groups were estimated in brain homogenate. Many fold rise in brain lead concentration at the end of the lead exposure rats was associated with increase in the lipid peroxides (LPO) level by 24.5% and catalase activity by 67%, as compared to that of control value. A significantly (P< 0.05) higher lipid peroxides level was recorded on days 3 and 10 and the activity of catalase was on day 3 of withdrawal of lead. A significant decrease in the protein bound thiol groups (P-SH) and increase in non- protein bound thiol groups (NP-SH) in the brain was observed at the end of the lead-exposure. It is concluded that a withdrawal period of 10 days was not sufficient to reduce the brain lead concentration to normal and subchronic exposure to lead increased NP-SH and LPO level, suggesting lead-related oxidative stress in brain.